Acetazolamide-Challenged Arterial Spin Labeling Detects Augmented Cerebrovascular Reserve After Surgery for Moyamoya. Issue 4 (6th December 2021) - Rao, Vaishnavi L.; Prolo, Laura M.; Santoro, Jonathan D.; Zhang, Michael; Quon, Jennifer L.; Jin, Michael; Iyer, Aditya; Yedavalli, Vivek; Lober, Robert M.; Steinberg, Gary K.; Yeom, Kristen W.; Grant, Gerald A.
Abstract : Background: Cerebrovascular reserve (CVR) inversely correlates with stroke risk in children with Moyamoya disease and may be improved by revascularization surgery. We hypothesized that acetazolamide-challenged arterial spin labeling MR perfusion quantifies augmentation of CVR achieved by revascularization and correlates with currently accepted angiographic scoring criteria. Methods: We retrospectively identified pediatric patients with Moyamoya disease or syndrome who received cerebral revascularization at ≤18 years of age between 2012 and 2019 at our institution. Using acetazolamide-challenged arterial spin labeling, we compared postoperative CVR to corresponding preoperative values and to postoperative perfusion outcomes classified by Matsushima grading. Results: In this cohort, 32 patients (17 males) with Moyamoya underwent 29 direct and 16 indirect extracranial-intracranial bypasses at a median 9.7 years of age (interquartile range, 7.6–15.7). Following revascularization, median CVR increased within the ipsilateral middle cerebral artery territory (6.9 mL/100 g per minute preoperatively versus 16.5 mL/100 g per minute postoperatively, P <0.01). No differences were observed in the ipsilateral anterior cerebral artery ( P =0.13) and posterior cerebral artery ( P =0.48) territories. Postoperative CVR was higher in the ipsilateral middle cerebral artery territories of patients who achieved Matsushima grade A perfusion, in comparison to those with grades B or C (25.8 versus 17.5 mL, P =0.02). The method of bypass (direct or indirect) did not alter relative increases in CVR (8 versus 3.8 mL/100 g per minute, P =0.7). Conclusions: Acetazolamide-challenged arterial spin labeling noninvasively quantifies augmentation of CVR following surgery for Moyamoya disease and syndrome.